An exploration of mechanism of high quality and yield of Gastrodia elata Bl. f. glauca by the isolation, identification, and evaluation of Mycena - Yu, En; Liu, Qun; Gao, Yugang; Li, Yaqi; Zang, Pu; Zhao, Yan; He, Zhongmei (Frontiers in Microbiology, 2023)
Gastrodia elata Bl. f. glauca is an important traditional Chinese medicinal plant. The yield and quality of Gastrodia elata Bl. have significantly decreased due to multigenerational asexual reproduction. Therefore, it is necessary to have sexual reproduction of Gastrodia elata Bl. to supplement the market supply. Seeds of G. elata Bl. have no endosperm, and their sexual reprod uction depends on the nutrients provided by the embryo cells infected by Mycena fungi to complete seed germination.However, Mycena fungi are small and have many species, and not all Mycena fungi can promote the germination of G. elata Bl. seeds. Therefore, it is of great significance to isolate and identify suitable germination fungi and explore the mechanism for improving the production performance and yield, and quality of G.